High-dose prescribed opioids are associated with increased risk of heroin use among United States military veterans. Issue 9 (September 2019) - Banerjee, Geetanjoli; Edelman, E. Jennifer; Barry, Declan T.; Crystal, Stephen; Gordon, Kirsha S.; Gordon, Adam J.; Gaither, Julie R.; Green, Traci C.; Kerns, Robert D.; Manhapra, Ajay; Moore, Brent A.; Fiellin, David A.; et al.
Abstract : Abstract: Despite evidence linking increased risk of opioid use disorder with specific opioid-prescribing patterns, the relationship between these patterns and heroin use is less understood. This study aimed to determine whether dose and duration of opioid prescriptions predict subsequent heroin use in United States veterans. We analyzed data from 2002 to 2012 from the Veterans Aging Cohort Study, a prospective cohort study. We used inverse probability of censoring weighted Cox regression to examine the relationship between self-reported past year heroin use and 2 primary predictors: (1) prior receipt of a high-dose opioid prescription (≥90 mg morphine equivalent daily dose), and (2) prior receipt of a long-term opioid prescription (≥90 days). Heroin use was ascertained using most recent value of time-updated self-reported past year heroin use. Models were adjusted for HIV and hepatitis C virus infection status, sociodemographics, pain interference, posttraumatic stress disorder, depression, and use of marijuana, cocaine, methamphetamines, and unhealthy alcohol use. In the final model, prior receipt of a high-dose opioid prescription was associated with past year heroin use (adjusted hazard ratio use = 2.54, 95% confidence interval: 1.26-5.10), whereas long-term opioid receipt was not (adjusted hazard ratio = 1.09, 95% confidence interval: 0.75-1.57). Patients receiving high-dose opioid prescriptions should be monitored for heroin use. These findings support current national guidelines recommending against prescribing high-dose opioids for treating pain. Abstract : Supplemental Digital Content is Available in the Text.In this study, veterans receiving high-dose prescription opioids (defined as ≥90 mg morphine equivalent daily dose) were at an increased risk of subsequent heroin use.